Disruptive desires and creative transgressions in Julie Taymor’s Across the Universe - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2023)
Julie Taymor’s career as a stage director, filmmaker, and costume designer has demonstrated the many possibilities of artistic adaptations that visualize characters, situations, emotions, and reality as a whole in new ways. Her works deconstruct classic texts and creative worlds to bring an altered visual experience through which she challenges the relationship between creation, adaptation, and perception. Taymor’s investigations seek to extract what an artistic work contains and imagine how it can be presented using different mediums. Whether it is adapting dramas for the stage, directing films, or staging operas, she finds her own versions by incorporating elements and art forms that reinvent a fresh way of telling a story.
Keywords: Julie Taymor; criticism and interpretation; women motion picture producers and directors